The evolutionary landscape of the chromatin modification machinery reveals lineage specific gains, expansions, and losses. - On, T.; Xiong, X.; Pu, S.; Turinsky, A.; Gong, Y.; Emili, A.; Zhang, Z.; Greenblatt, J.; Wodak, S.J.; Parkinson, J. (Proteins, 2010)
Model organisms such as yeast, fly, and worm have played a defining role in the study of many biological systems. A significant challenge remains in translating this information to humans. Of critical importance is the ability to differentiate those components where knowledge of function and interactions may be reliably inferred from those that represent lineage-specific innovations. To address this challenge, we use chromatin modification (CM) as a model system for exploring the evolutionary properties of their components in the context of their known functions and interactions. Collating previously identified components of CM from yeast, worm, fly, and human, we identified a "core" set of 50 CM genes displaying consistent orthologous relationships that likely retain their interactions and functions across taxa. In addition, we catalog many components that demonstrate lineage specific expansions and losses, highlighting much duplication within vertebrates that may reflect an expanded repertoire of regulatory mechanisms. Placed in the context of a high-quality protein-protein interaction network, we find, contrary to existing views of evolutionary modularity, that CM complex components display a mosaic of evolutionary histories: a core set of highly conserved genes, together with sets displaying lineage specific innovations. Although focused on CM, this study provides a template for differentiating those genes which are likely to retain their functions and interactions across species. As such, in addition to informing on the evolution of CM as a system, this study provides a set of comparative genomic approaches that can be generally applied to any biological systems.